Chapter 3 Brothers Re-United! Federal Citizenship in Socialist Yugoslavia - Štiks, Igor (Bloomsbury Academic, 2015)
The creation of the multinational federation involved at the same time the re-creation of the Yugoslav polity and a laborious construction of the sub-state entities and their own political communities. The creation of republican citizenships and the Yugoslav common two-tier or bifurcated citizenship was part and parcel of this intensive construction of modern states within a larger multinational federation. Citizenship was an important attribute of the republics' statehood, although it was rarely mentioned as such by the authorities and was almost completely neglected by scholars. The institution will show its resilience and importance only later. The constitutional process at the same time seemed endless: post-war Yugoslavia introduced three constitutions between 1945 and 1963, which shaped the country in a different way, oscillating between Yugoslav socialist unity and the decentralization process empowering the republics. The establishment of multinational federation at the formal level and the Yugoslav brand of 'self-managing socialism' at the ideological level provided foundation for the new Yugoslav community. However, constant changes opened the whole construction, including citizenship regime, for redefinitions in the next period.